2022
DOI: 10.3389/fendo.2022.1025032
|View full text |Cite
|
Sign up to set email alerts
|

Free triiodothyronine levels and age influences the metabolic profile and COVID-19 severity parameters in euthyroid and levothyroxine-treated patients

Abstract: Metabolic reprogramming is required to fight infections and thyroid hormones are key regulators of metabolism. We have analyzed in hospitalized COVID-19 patients: 40 euthyroid and 39 levothyroxine (LT4)-treated patients in the ward and 29 euthyroid and 9 LT4-treated patients in the intensive care unit (ICU), the baseline characteristics, laboratory data, thyroid-stimulating hormone (TSH), free thyroxine (FT4), free triiodothyronine (FT3), the FT3/FT4 ratio, 11 antiviral cytokines and 74 metabolomic parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Amich et al also investigated thyroid dysfunction in COVID-19 patients divided into two pre-selected groups: (i) 334 individuals who contracted COVID-19 and (ii) 122 individuals without COVID-19 [139]. Electronic records showed that most COVID-19 patients (86.6%) were in a euthyroid state before infection, meaning their thyroid was functioning appropriately.…”
Section: Thyroid Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Amich et al also investigated thyroid dysfunction in COVID-19 patients divided into two pre-selected groups: (i) 334 individuals who contracted COVID-19 and (ii) 122 individuals without COVID-19 [139]. Electronic records showed that most COVID-19 patients (86.6%) were in a euthyroid state before infection, meaning their thyroid was functioning appropriately.…”
Section: Thyroid Disordersmentioning
confidence: 99%
“…However, noteworthy variations in TSH levels (p = 0.009) and ferritin (p = 0.031) were observed between euthyroid and LT4-treated patients in the ward, along with TSH (p = 0.044) and FT4 (p = 0.012) in the ICU. Moreover, parameters indicating an unfavorable prognosis were related to low FT3 levels and/or the age of the patient [139].…”
Section: Thyroid Disordersmentioning
confidence: 99%